2016
DOI: 10.1126/scitranslmed.aad7121
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics, birth mode, and diet shape microbiome maturation during early life

Abstract: Early childhood is a critical stage for the foundation and development of both the microbiome and host. Early-life antibiotic exposures, cesarean section, and formula feeding could disrupt microbiome establishment and adversely affect health later in life. We profiled microbial development during the first two years of life in a cohort of 43 US infants, and identify multiple disturbances associated with antibiotic exposures, cesarean section, and diet. Antibiotics delayed microbiome development and suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

67
1,149
9
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 1,131 publications
(1,244 citation statements)
references
References 69 publications
67
1,149
9
19
Order By: Relevance
“…; however, effects of feeding on Lactobacillus abundance are inconsistent across other studies. Increased proportions of Lactobacillus, 25,26,48,54 as well as greater abundances of L. gasseri 28,47 in BF compared to FF infants have been reported, whereas other studies found opposite results 16,52,53 or reported intergroup variability and instability over time. 27,43 A greater prevalence 15 and higher proportion 24 and total counts 16,46 of C. difficile in FF compared to BF infants, as well as, significantly more Peptostreptococcaceae, 31 Akkermansia, 15 Veillonella, and Enterococcus 28 have been described.…”
Section: (Finland)mentioning
confidence: 66%
See 3 more Smart Citations
“…; however, effects of feeding on Lactobacillus abundance are inconsistent across other studies. Increased proportions of Lactobacillus, 25,26,48,54 as well as greater abundances of L. gasseri 28,47 in BF compared to FF infants have been reported, whereas other studies found opposite results 16,52,53 or reported intergroup variability and instability over time. 27,43 A greater prevalence 15 and higher proportion 24 and total counts 16,46 of C. difficile in FF compared to BF infants, as well as, significantly more Peptostreptococcaceae, 31 Akkermansia, 15 Veillonella, and Enterococcus 28 have been described.…”
Section: (Finland)mentioning
confidence: 66%
“…Many studies have reported that BF infants are colonized with higher proportions of microbes from the phylum Actinobacteria and less Firmicutes than FF infants. 23,25,26,28,33 Other studies report that BF infants have similar levels of Actinobacteria and Firmicutes 28,30 but lower proportions of Bacteroidetes 31,36 and Proteobacteria 26,28 compared to FF infants.…”
Section: (Finland)mentioning
confidence: 99%
See 2 more Smart Citations
“…Antibiotics use during infancy is closely associated with the changes in the composition of gut microbiota which last for more than 6 months. To resolve the origin of gut microbiota and thoroughly research the possible impact of antibiotics use and other environmental factors on gut microbiota, a team of researchers from the Massachusetts General Hospital (MGH) and the Broad Institute selected a cohort of 43 U.S. infants and analyzed microbial development during the first 2 years of life systematically [19]. They identified multiple disturbances associated with antibiotic exposures, cesarean section, and formula feeding.…”
Section: Antibiotic Use Disrupts Structure Of Gut Flora and Metabolicmentioning
confidence: 99%